Central Nervous System Manifestations of COVID-19: A Critical Review and Proposed Research Agenda. (16th March 2022) - Hewitt, Kelsey C.; Marra, David E.; Block, Cady; Cysique, Lucette A.; Drane, Daniel L.; Haddad, Michelle M.; Łojek, Emilia; McDonald, Carrie R.; Reyes, Anny; Eversole, Kara; Bowers, Dawn
Abstract: Objective: On March 11, 2020, the World Health Organization declared an outbreak of a new viral entity, coronavirus 2019 (COVID-19), to be a worldwide pandemic. The characteristics of this virus, as well as its short- and long-term implications, are not yet well understood. The objective of the current paper was to provide a critical review of the emerging literature on COVID-19 and its implications for neurological, neuropsychiatric, and cognitive functioning. Method: A critical review of recently published empirical research, case studies, and reviews pertaining to central nervous system (CNS) complications of COVID-19 was conducted by searching PubMed, PubMed Central, Google Scholar, and bioRxiv. Results: After considering the available literature, areas thought to be most pertinent to clinical and research neuropsychologists, including CNS manifestations, neurologic symptoms/syndromes, neuroimaging, and potential long-term implications of COVID-19 infection, were reviewed. Conclusion: Once thought to be merely a respiratory virus, the scientific and medical communities have realized COVID-19 to have broader effects on renal, vascular, and neurological body systems. The question of cognitive deficits is not yet well studied, but neuropsychologists will undoubtedly play an important role in the years to come.